2024
DOI: 10.4014/jmb.2310.10037
|View full text |Cite
|
Sign up to set email alerts
|

Ozonated Sunflower Oil (OSO) Alleviates Inflammatory Responses in Oxazolone-Induced Atopic Dermatitis (AD)-Like Mice and LPS-Treated RAW 264.7 Cells

Su-Young Kim,
Jung Ok Lee,
Sue Lee
et al.

Abstract: Ozone, a highly reactive oxidant molecule, is widely used as a complementary therapy for various skin diseases, including wound healing, pressure ulcers, diabetic foot, and infections. However, there is limited research on the effectiveness of ozone for atopic dermatitis (AD). Ozonated sunflower oil (OSO) is an active ingredient obtained from partially ozonated sunflower oil (SO). OSO markedly reduced the LPS-induced increase in IL-1β and nitric oxide (NO) levels in RAW 264.7 mouse macrophage cells. Oxazolone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 45 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…Ozonated HA-PO possesses an anti-inflammatory effect on the skin diseases of mice and humans [78]. The symptoms of AD, such as scaling, excoriation, erythema, edema, epidermal thickness, infiltration of mast cell, serum levels of IgE, and spleen weight and lymph node length are decreased by treatment with ozonated HA-PO in an oxazolone (Oxz)-induced AD mouse model [79]. In addition, skin hydration function and FLG are recovered by treatment with ozonated HA-PO through the downregulation of IL-4/signal transducers and activators of the transcription (STAT) 3/extracellular signalregulated kinase (ERK) pathway in an Oxz-induced AD mouse model [79].…”
Section: Helianthus Annuus Plant Oil (Ha-po)mentioning
confidence: 99%
See 2 more Smart Citations
“…Ozonated HA-PO possesses an anti-inflammatory effect on the skin diseases of mice and humans [78]. The symptoms of AD, such as scaling, excoriation, erythema, edema, epidermal thickness, infiltration of mast cell, serum levels of IgE, and spleen weight and lymph node length are decreased by treatment with ozonated HA-PO in an oxazolone (Oxz)-induced AD mouse model [79]. In addition, skin hydration function and FLG are recovered by treatment with ozonated HA-PO through the downregulation of IL-4/signal transducers and activators of the transcription (STAT) 3/extracellular signalregulated kinase (ERK) pathway in an Oxz-induced AD mouse model [79].…”
Section: Helianthus Annuus Plant Oil (Ha-po)mentioning
confidence: 99%
“…The symptoms of AD, such as scaling, excoriation, erythema, edema, epidermal thickness, infiltration of mast cell, serum levels of IgE, and spleen weight and lymph node length are decreased by treatment with ozonated HA-PO in an oxazolone (Oxz)-induced AD mouse model [79]. In addition, skin hydration function and FLG are recovered by treatment with ozonated HA-PO through the downregulation of IL-4/signal transducers and activators of the transcription (STAT) 3/extracellular signalregulated kinase (ERK) pathway in an Oxz-induced AD mouse model [79]. Moreover, the levels of nitrite oxide (NO) and iNOS are inhibited by treatment with ozonated HA-PO through downregulation of IL-1β and TNF-α via MAPK and the NF-κB pathway in serum and skin tissues in an Oxz-induced AD mouse model [79].…”
Section: Helianthus Annuus Plant Oil (Ha-po)mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a remarkable effect of OSO in treating endometriosis in mares [12,16] and demodicosis in dogs [13] logged the broad-spectrum antimicrobial role of OSO. Besides the antimicrobial effect, we have recently disclosed the curative effect of OSO against atopic dermatitis (AD) in the mouse model [17], where we observed that the topical application of OSO significantly affected the infiltration of mast cells, filaggrin, and thymic stromal lymphopoietin (TSLP). In addition, OSO was logged for diminished serum Ig E, TNF-α, and IL-1β levels and displayed a significant antioxidant and anti-inflammatory effect by inhibiting the IL-4/STAT3/MAPK pathway and expression of NFκB [17].…”
Section: Introductionmentioning
confidence: 99%